DEINING THE NET OF GEOMAGNETIC REPEAT STATIONS IN THE REPUBLIC OF KOSOVO (Geologica Macedonica, 2022)
This paper presents the necessary procedures that should be conducted for definition of net of repeat stations on the territory of the Republic of Kosovo, according the INTERMAGNET standards. (Rasmussen and Kerridge, 2002). For complete monitoring of the geomagnetic field in a given space, it is necessary to have a basic network of stations for periodic field observation and a geomagnetic observatory that permanently measures the temporal changes of the geomagnetic field. To define the coefficients of dependence of the geomagnetic field on the latitude and longitude of a given point for a certain space (usually a state), in addition to the existence of a geomagnetic observatory which is a benchmark, requires a relatively homogeneous network of geomagnetic stations. For that purpose, detailed field measurement should be performed for definition of the several repeat stations which will compose the net of the repeat stations on the territory of the Republic of Kosovo. The basic network of geomagnetic stations is used for periodic measurements of those points in an interval of 3 to 5 years. For a given epoch (period of five years) the value of any component of the geomagnetic field can be calculated for a given point belonging to the space (state) that covers the geomagnetic observatory with coordinates φo and λo.
Keywords: procedures; repeat stations; definition; net; intermagnet